Back Cover: Structural Biology of Cisplatin Complexes with Cellular Targets: The Adduct with Human Copper Chaperone Atox1 in Aqueous Solution (Chem. Eur. J. 37/2014). Issue 37 (8th September 2014) - Calandrini, Vania; Nguyen, Trung Hai; Arnesano, Fabio; Galliani, Angela; Ippoliti, Emiliano; Carloni, Paolo; Natile, Giovanni
<x xml:space="preserve">Abstract</x> Hybrid QM/MM simulations and molecular spectroscopy provide structural insights on cisplatin binding to the copper transporter Atox1 in water solution. A molecular model of the platinated protein is provided. In this model, the Pt atom binds to Cys12 and Cys15 while retaining its two cis ammine ligands. The calculated 1H, 13C, and 15N NMR chemical shifts and CD spectra of this model are in accord with experiment. For the complete story see the Full Paper by P. Carloni et al. on page 11719 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>